Inter-regional educational migrations in Russia in 2017–2019: gender and spatial aspects - Bezverbny, Vadim A.; Mikryukov, Nikolai Y.; Sitkovskiy, Arseniy M. (The New Research of Tuva, 2024)
The article explores the gender and spatial aspects of interregional educational migration in Russia between 2017 and 2019, with a particular focus on young people aged 15–16 and 17–18. The study uncovers trends in the appeal of different regions for educational migrants and identifies gender differences in the choice of educational pathway and subsequent labor mobility.The results of the study indicate that many Russian regions, including central Russia, the Rostov and Sverdlovsk regions, the Krasnoyarsk Krai and the Khabarovsk Krai, are attractive for educational migration. However, the Republic of Tatarstan and Primorsky Krai, despite significant investment in educational infrastructure, were found to be less so. Gender analysis showed that women's educational migration tended to focus on the largest agglomerations and western regions, while men's migration was often linked to military education and service.The situation in the Republic of Tuva stands out as a unique case within the context of this study. Unlike in other regions, where female educational migration often has a low return, in Tuva, there is a significant return of young women aged 19-25.The article proposes several recommendations to address gender imbalances, such as a more equal distribution of resource revenues and investments in economic diversification at the national and regional levels.
Keywords: gender studies; regional demography; interregional migration; youth migration; educational migration; spatial development; Russia; region of Russia; Republic of Tuva